UJI AKTIVITAS KOMBINASI EKSTRAK AIR LIDAH BUAYA ( Aloe vera L.) DAN AKAR MANIS (Glycyrrhiza glabra L.) SEBAGAI PENYUBUR RAMBUT - Sulistiorini Indriaty; Teti Indrawati; Shelly Taurhesia (Universitas Ahmad Dahlan, 2016)
Aloe vera (Aloe vera L.) contains amino acids, vitamins, folic acid, and liquorice (Glycyrrhiza glabra L) containing glisirizin, and flavonoids, which have properties as fertilizer hair. This study aims to obtain a combination of extracts with activity most optimal fertilizer hair, made 3 combination with a combination of 1 (the water extract of liquorice concentration of 2.5% and 7.5% aloe vera), a combination of 2 (the water extract of liquorice concentrations of 2, 5% and 2.5% aloe vera), and combinations of 3 (the water extract of liquorice concentration of 5% and 7.5% aloe vera). Testing the activity of hair growth is done by measuring the rate of hair growth, hair growth acceleration and weight of rabbit hair for 28 days. Rabbit hair growth results showed the combination 1 has an average length of the largest hair with hair growth rate value of 2.97 cm, accelerated hair growth amounted to 0.15 cm / day on day 7 and weighing 0.13 gram hair.